Impact of Influencer Attractiveness, Credibility on Parasocial Interaction, Purchase Intentions: Moderating Congruence - Annisa, Zahrah; Ariella, Shanon Eden; Rahman, Fathony; Prasetya, Prita (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The increasingly widespread use of social media has risen one profession of being a social media influencer. An interesting fact is that these influencers have a strong influence on Instagram as famous individuals who receive a lot of public attention. Therefore, now influencers are creating their own product lines, namely influencer-branded products. This research aims to test the influence of influencer credibility and attractiveness on parasocial interactions between influencers and customers and to determine the influence of parasocial interactions on purchase intentions of influencers-branded products. This research also aims to test the influence of congruency between consumers and influencers, influencers and products, and products and consumers as moderating variables. 227 respondents were obtained using an online survey of quantitative methods which was then analyzed using SEM AMOS 26 program. The results of this study is that influencer’s attractiveness, trustworthiness, and expertise have a significant influence on parasocial interaction and parasocial interaction has a significant impact on purchase intention. In addition, the moderation variable of consumer and influencer’s congruence, consumer and product congruence, and influencer and product congruence also have a significant influence that moderates the effect of parasocial interaction and purchase intention in which the influence is stronger if the moderators are high